2023
DOI: 10.3389/fmicb.2023.1076011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of altitude on the gut microbiome and metabolomics of Sanhe heifers

Abstract: IntroductionExtreme environments at high altitudes pose a significant physiological challenge to animals. We evaluated the gut microbiome and fecal metabolism in Sanhe heifers from different altitudes.MethodsTwenty Sanhe heifers (body weight: 334.82 ± 13.22 kg, 15-month-old) selected from two regions of China: the Xiertala Cattle Breeding Farm in Hulunbeier, Inner Mongolia [119°57′ E, 47°17′ N; approximately 700 m altitude, low altitude (LA)] and Zhizhao Dairy Cow Farm in Lhasa, Tibet [91°06′ E, 29°36′ N; appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
(49 reference statements)
1
2
0
Order By: Relevance
“…This study explored the ruminal microbes and found that there were significant differences at different taxonomic levels. Firmicutes and Bacteroidetes, which mainly participate in the absorption and digestion of carbohydrates and proteins, had the highest abundance at the phylum level, consistent with a previous study [ 30 , 31 ]. Tenericutes, Kiritimatiellaeota, and Elusimicrobia were the three significantly different microbial phyla, which had greater relative abundance in group C. Tenericutes and Elusimicrobia are minor members, and their role in rumen is uncertain [ 32 , 33 ].…”
Section: Discussionsupporting
confidence: 92%
“…This study explored the ruminal microbes and found that there were significant differences at different taxonomic levels. Firmicutes and Bacteroidetes, which mainly participate in the absorption and digestion of carbohydrates and proteins, had the highest abundance at the phylum level, consistent with a previous study [ 30 , 31 ]. Tenericutes, Kiritimatiellaeota, and Elusimicrobia were the three significantly different microbial phyla, which had greater relative abundance in group C. Tenericutes and Elusimicrobia are minor members, and their role in rumen is uncertain [ 32 , 33 ].…”
Section: Discussionsupporting
confidence: 92%
“…Altitude change has emerged as a major driving factor of fluctuations in the gut microbiota, influencing both bacterial composition and function. Different altitudes have been found to induce varying changes in the composition and abundance of the gut microbiota ( Zhang et al, 2023a ). A prior study investigating the characteristics of the intestinal microbiota of six geographical populations of Macaca mulatta in China found that M. mulatta populations in Tibet exhibited the highest intestinal microbiota diversity and possessed the highest number of unique microbiota ( Zhao et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the same body weight groups (HOB vs. LOB, HN vs. LN), the main dominant bacterium was Romboutsia , which was mainly associated with the metabolism of nucleotide and amino acid compounds. The analysis of the effect of altitude on Sanhe heifers' gut microbiota and metabolism found that Romboutsia was associated with the metabolism of purine pyrimidines and amino acids (Zhang et al, 2023 ). Another study found that some potential probiotics, including Christensenellaceae_R-7_group, Ruminococcus_1, Romboutsia, Alloprevotella, E. coprostanoligenes , and Clostridium , were enriched in the rumen of high-altitude yaks.…”
Section: Discussionmentioning
confidence: 99%